The Hadron Production in π–C Interaction at 40 GeV/c and QCD Phase Transition - Ts, Baatar; R, Togoo; A.I, Malakho; B, Otgongerel; G, Sharkhuu; T, Tulgaa (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this paper, we proposed to study the phase transition process to use the new pair of variables, the temperature T...